Oral Delivery of Encapsulated All-Trans Retinoic Acid Ameliorates Disease in Rodent Models of Colitis. Issue 3 (21st August 2021) - Nicoletti, Ferdinando; Hammer, Laura; Furtado, Stacia; Mangano, Katia; Mathiowitz, Edith; Green, Benjamin; Auci, Dominick L
Abstract: Background: All-trans retinoic acid (ATRA) is a biologically active isomer of retinoic acid (RA). Topical ATRA (retin-a, retin-a micro, atralin, renova, and avita) is the active pharmaceutical ingredient for FDA-approved treatments for acne and skin wrinkles. Oral formulations (Vesanoid) treat acute promyelocytic leukemia, but oral dosing can induce severe side effects. Despite benefits in various rodent models of inflammatory bowel disease (IBD), toxicity and controversial clinical observations have diminished enthusiasm for ATRA IBD clinical trials. To circumvent these issues and to use ATRA's key role in maintaining gut tolerance, we developed a poly(lactic-co-glycolic acid) (PLGA) microsphere (MS) encapsulated ATRA formulation aimed at directing ATRA delivery to immune structures of the gut, limiting systemic exposure. Initially, ATRA MS was developed as a component of a combinatorial product (TreXTAM) that also contained encapsulated transforming growth factor (TGF)-β and ATRA in a 1:2 w/w ratio. Although the combination was optimal, benefit was also observed when ATRA MS was given alone in the CD4+ CD25-T-cell adoptive transfer (ACT) colitis model. Methods: We used the ACT and DSS-induced murine models of colitis to expand on the dose-dependent effects of oral ATRA MS when given alone. The DSS model was also used to compare the efficacy of ATRA MS and soluble ATRA, while healthy animals were used to compare the pharmacokinetics of the two drugs. Results: In both the ACT and DSS-induced murine models of colitis, ATRA MS was observed to be effective in ameliorating disease. ATRA MS was also observed to be more effective than soluble ATRA in these models and displayed more favorable pharmacokinetics. Conclusions: We suggest ATRA MS, as a standalone product, may attenuate IBD and perhaps limit fibrosis, while limiting systemic side effects.